Eco-Friendly Beauty: What an Eco-Branding and Consumer Values Drive Purchase Intentions - Pristiana Widyastuti (Newinera Publisher, 2024)
This study investigates the relationship between eco-branding and eco-consumerism toward purchase intention for local beauty products in Indonesia. The total sample size was determined as 120 samples. The study employed purposive sampling, a non-probability sampling method where respondents were selected based on predefined criteria. The study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) as the primary analytical technique. The data analysis was conducted using SmartPLS, a powerful tool for PLS-SEM. The research findings indicate that eco-branding significantly impacts purchase intention for beauty products in Indonesia. Consumers are strongly inclined toward products that demonstrate their commitment to sustainability through various environmental practices. Eco-consumerism significantly influences purchase intention for beauty products. Respondents expressed that choosing eco-friendly products is not only a moral obligation but also a reflection of their sustainability and environmental stewardship values.